Eyes or mouth? Exploring eye gaze patterns and their relation with early stress perception in European Portuguese. (30th April 2020) - Cruz, Marisa; Butler, Joseph; Severino, Cátia; Filipe, Marisa; Frota, Sónia
Abstract : Previous research has shown that eye gaze patterns relate to language development, with more attention to the mouth signaling ongoing acquisition. We examined infants' eye gaze in a stress perception experiment, in which European Portuguese (EP) learning infants showed a preference for the iambic stress pattern. Specifically, we asked whether there was a relation between eye gaze patterns and the preferred stress pattern. Eye gaze patterns of 25 monolingual typically developing infants aged 5–6 months old were examined using eye-tracking. Our results show that, although an interaction between looks to the area of interest (face, eyes, mouth, and arm) and stress preference was not found, eye gaze to the mouth region (and to the face) was modulated by the stress pattern, with more attention to the mouth in infants that do not show an iambic preference. These findings add further support for infants' use of eye gaze in early language development. They also highlight the need for multimodal approaches for a better understanding of language development. In the particular case of the challenging topic of the acquisition of stress in European Portuguese, they provide converging evidence for an advantage of iambic stress in early development. (195 words).